Open Educational Resources (OERs) and Metadata: The Future of Textbook Access and Usability - Adamich, Tom (Technicalities, 2011)
According to Baumann in "E-books: A New School of Thought," the average public university student spends $1,222 on textbooks (as part of the nearly $26,273 the same student spends annually to attend a public four-year college or university).2 Another big advantage of using the OER, compared to a more traditional educational resource, is its modular structure - that ability, as mentioned earlier, to be utilized as a part or piece in order to address a specific educational need or effectively represent a particular concept. According to the "Comparison of Metadata of THECB [Texas Higher Education Coordinating Board] and Other Learning Object Repositories," the Orange Grove Digital Repository uses the aforementioned Southern Regional Education Board's SCORE documentation.8 SCORE is based on the Institute of Electrical and Electronics Engineers (IEEE) Draft Standard for Learning Object Metadata (LOM) - a Dublin Core derivative - and uses IEEE LOM and Gateway to Educational Materials (GEM) controlled vocabularies as sources for subject terms.